Protein digestibility and bioavailability in an F2 mouse cross between the selected fat mouse line and an M2 congenic line carrying the anti‐obesity and anti‐diabetic Tst allele. Issue 4 (12th October 2021) - Pirman, Tatjana; Mrak, Vesna; Fonseca, Rita; Horvat, Simon
Abstract: The study was performed to investigate protein digestibility and utilization in an F2 cross (M2‐F2 cross) between the selected Fat (F) line and an M2 congenic line. The congenic M2 line carried the Fob3b2 quantitative trait locus (QTL) from the selected Lean (L) line previously shown to contain the Tst gene with leanness, anti‐diabetic and resistance to diet‐induced obesity effects. The main objective of the study was to test if some of the effects on leanness and obesity resistance of the L‐line Fob3b2 could also be due to the effect of this QTL on nutrient digestibility and bioavailability. The F2 littermates carrying either the Fat line segment within the Fob3b2 region or the L‐line were compared when fed the high‐fat diet. Eleven mice per genotype were individually housed in metabolic cages. In 5‐day experimental period, body mass and diet intake were measured. The part of study was done on the F and L line and tested the difference in apparent protein digestibility on low‐fat (LFD) and high‐fat (HFD) diet. The nitrogen content was determined in the diet, faeces, and urine based on which, the apparent protein digestibility, apparent protein biological value and apparent net protein utilization were calculated There were no significant differences in any of these parameters on congenic line, confirming that the phenotypic effect on adiposity between the genotypes in the M2‐F2 population was not due to the differential effect of the Fob3b2 locus carrying the Tst gene on protein utilization. We conclude that the observed phenotypic effects of this gene region are due to direct metabolic actions rather than the effects on nutrient absorption and nitrogen utilization since there were no differences in apparent protein digestibility between L and F lines, irrespective to HFD or LFD. The age of animals had significant effect on the level of digestibility.